Treatment Strategies in Early Rheumatoid Arthritis Methotrexate Management: Results From a Prospective Cohort. Issue 8 (5th July 2020) - Moura, Cristiano S.; Schieir, Orit; Valois, Marie‐France; Thorne, Carter; Bartlett, Susan J.; Pope, Janet E.; Hitchon, Carol A.; Boire, Gilles; Haraoui, Boulos; Hazlewood, Glen S.; Keystone, Edward C.; Tin, Diane; et al.
Abstract : Objective: To assess real‐world practice patterns surrounding treatment initiation and adjustments over time for methotrexate (MTX) and non‐MTX–based treatment strategies in early rheumatoid arthritis (RA). Methods: We studied a multicenter, incident early RA cohort (enrolled 2007–2017 within 1 year of symptoms) who fulfilled American College of Rheumatology/European League Against Rheumatism criteria. Adult patients with RA were eligible if treatment with MTX (± other disease‐modifying antirheumatic drugs [DMARDs]) was initiated within 90 days of cohort entry. We compared time until treatment change for 4 initial MTX‐based therapies and time to second treatment change after the first change. The definition of treatment change included changing of route for MTX monotherapy, adding or stopping a DMARD or biologic, and changing dose/frequency of a DMARD or biologic. Results: There was great variability of treatment at initiation and during therapy adjustment. In 1, 484 patients with early RA, the majority initiated MTX monotherapy (oral or subcutaneous [SC]). Patients receiving SC MTX monotherapy changed treatment less (45% versus 79%) and remained on treatment longer (hazard ratio [HR] 0.52 [95% confidence interval (95% CI) 0.4–0.67]) than those receiving oral MTX monotherapy. Most therapy adjustments involved adding a DMARD or changing to a non‐MTX DMARD. Those adults taking biologics and who were receiving triple therapy had a longer time without treatment change (HR 0.26 [95% CI 0.16–0.42] and HR 0.57 [95% CI 0.38–0.85], respectively). Conclusion: We found large variability in the way MTX‐based therapies are prescribed in clinical practice. Our findings support the use of SC MTX monotherapy or MTX combination as initial therapy. For subsequent treatment after initial MTX‐based therapy, those patients initiating either biologics or triple therapy had a longer time to treatment change than oral MTX monotherapy.